CAD-CAM Technology: A literature review - Mohammed A. Abdulla; Hala Khuder Ali; Raghad S Jamel (University of Mosul, College of Dentistry, 2020)
Aims: this article focus some of an important aspects related to a CAD/ CAM technology including: applications, designing, construction by the use of computerized controlling machines that developed very fastly in the last two decays. Conclusions: CAD/CAM technology is attained finished different dental restorations through designing and milling processes of a two dimensional or three dimensional models using different ready blocks by numerical controlled machines.